Perlindungan Hukum Kreditur Konkuren dengan Menggunakan Mekanisme Gugatan Lain-Lain dalam Undang-Undang Nomor 37 Tahun 2004 tentang Kepailitan dan Penundaan Kewajiban Pembayaran Utang (Deposisi: Jurnal Publikasi Ilmu Hukum, 2024)
In the PKPU process, problems often occur, especially when the debtor defaults, which can trigger disputes between creditors, especially concurrent creditors who receive the last payment. Therefore, there is a mechanism for other lawsuits as a legal tool to protect the rights of concurrent creditors. The purpose of writing this article is to explain the legal protection for concurrent creditors through the mechanism for other lawsuits in the context of debt payment suspension and bankruptcy, based on Law Number 37 of 2004. This study uses a normative legal method with a statutory and case approach to analyze relevant legal provisions and practices in the field. The results of the study indicate that although Law Number 37 of 2004 provides a clear legal framework for the protection of concurrent creditor rights, there are still challenges in its implementation. Obstacles such as inconsistent law enforcement and lack of debtor awareness of creditor rights affect the effectiveness of such protection. Therefore, it is important for creditors to understand and utilize existing legal mechanisms to protect their interests during the bankruptcy process.